Mycotheism - Yeo, Nicole Jia Ying (2017)
Mycotheism — the rise of a new fungi religion where the omnipresent fungi gods are respore-nsible for prolonging life, or sending us to our deaths. This religion is an amalgamation of artistic, scientific and spiritual elements. It intertwines fact with fantasy, enticing the believer into a world of wonder where things are better than the reality we live in — or are they? Through the use of visual metaphors, allegories, puns, illustrations and visual mapping, this project imparts the sacred laws and truths of Mycotheism and prophesying the fate of humanity.